The impact of general anesthesia on methionine metabolism during cardiopulmonary bypass - Yu. S. Polushin; T. F. Subbotina; N. S. Molchan; A. A. Zhloba (Вестник анестезиологии и реаниматологии)
It has been found out that methylation of nucleic acids, proteins and low-molecular substrates is necessary to renew cellular structures, their restoration and cytoprotection. Methionine plays the most important role in this process but whether its metabolism changes during anesthesia and how different anesthetics affect it, has not yet been studied.The objective: to study the metabolism of methionine during cardiopulmonary bypass when the direct myocardial revascularization is performed and the impact of the anesthetics used (propofol, desflurane, and sevoflurane) on methionine metabolism.Subjects and methods: 74 patients who underwent surgery due to coronary heart disease with cardiopulmonary bypass were enrolled in the study. The patients were divided into three groups by the anesthetic used (desflurane, sevoflurane, propofol). Levels of methionine, homocysteine, cysteine, and taurine were tested in the blood collected from veins and jugular vein before the aorta clamping and after the release of clamps.Results. In all three groups, lower levels of methionine and a higher level of homocysteine were observed after the release of clamps from the aorta, especially in the jugular vein. The most significant consumption of methionine was noted when propofol was used. In the same group, the exocytic release of homocysteine into the blood and the formation of cysteine were significantly lower. No significant difference was observed in the effect of desflurane and sevoflurane on methylation.Conclusion. During the anoxia, the consumption of methionine increases significantly but the intensity of demethylation/remethylation depends on the anesthetics used during anesthesia. The most significant decrease in the level of methionine as well as the remethylation of homocysteine into methionine occurs with the use of propofol, rather than inhalation anesthetics which may be a consequence of desflurane and sevoflurane cytoprotective properties.